Analysis of Factors Affecting the Volume of Coffee Export in Central Aceh to The United States - Talbani Farlian; Zahrani Masthura (Agriekonomika, 2021)
U.S is the largest export destination of Gayo coffee from Central Aceh Regency, Aceh Province because the United States is the largest coffee importer country and has the largest export market potential for Indonesian coffee. Therefore, this study aims to find out the economic factors that affect the volume of coffee export from Central Aceh to the U.S market. Data in this study used time series data during the period 2015-2020. This research is influenced by several independent variables, including Total Coffee Production in Central Aceh (X1), International Coffee Prices (X2), and Rupiah Exchange Rate Against the USDollar (X3). The result of this study is that the International Coffee Price and Rupiah Exchange Rate Against the U.SDollar each significantly affect the Volume of Coffee Export in Central Aceh to the United States. While variable total productionhas no significant effect significantly